2017
DOI: 10.1128/iai.00270-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Staphylococcus aureus-Infected Mice Reveals Differential Temporal and Spatial Expression Patterns of fhuD2

Abstract: (2017) In vivo analysis of staphylococcus aureus-infected mice reveals differential temporal and spatial expression patterns of fhuD2. Infection and Immunity, 85(10), e00270-17. (doi:10.1128/IAI.00270-17) This is the author's final accepted version.There may be differences between this version and the published version. Staphylococcus aureus is an opportunistic human pathogen and a major cause of invasive 21 infections such as bacteremia, endocarditis, pneumonia and wound infections. FhuD2 is a 22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…This evidence was consistent with DIBI sequestering host Fe within wounds or on the mucosal surfaces of the nares, i.e., host Fe supplies that would otherwise have been available to support S. aureus infection. The in vivo results are especially significant given the recent demonstration of S. aureus upregulating one of its key iron acquisition systems during experimental infection ( Bacconi et al, 2017 ) revealing the bacterium is forced to compete continuously for host Fe during the course of infection. The previous finding that various Fe acquisition genes are upregulated in S. aureus while colonizing the nares ( Chaves-Moreno et al, 2016 ) provides further evidence that host Fe availability is important for staphylococcal growth in vivo and that effective sequestration of host iron might suppress nares colonization and other infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This evidence was consistent with DIBI sequestering host Fe within wounds or on the mucosal surfaces of the nares, i.e., host Fe supplies that would otherwise have been available to support S. aureus infection. The in vivo results are especially significant given the recent demonstration of S. aureus upregulating one of its key iron acquisition systems during experimental infection ( Bacconi et al, 2017 ) revealing the bacterium is forced to compete continuously for host Fe during the course of infection. The previous finding that various Fe acquisition genes are upregulated in S. aureus while colonizing the nares ( Chaves-Moreno et al, 2016 ) provides further evidence that host Fe availability is important for staphylococcal growth in vivo and that effective sequestration of host iron might suppress nares colonization and other infections.…”
Section: Discussionmentioning
confidence: 99%
“…For our DIBI/antibiotic interaction studies, we also deliberately provided only a sub-inhibitory amount of DIBI so as to ensure a physiological condition of Fe-restricted growth, i.e., growth restricted but not fully arrested. This physiological state of Fe-restricted growth could also have clinical relevance to infection noting that S. aureus has been shown to respond to in vivo Fe restriction through upregulation of its Fe acquisition mechanisms throughout the entire course of infection ( Chaves-Moreno et al, 2016 ; Bacconi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that staphylococcal growth and turnover are high during both human and murine nares carriage with active bacterial replication in the nose (18). DIBI restricts iron supply to S. aureus isolates impairing their growth (12), and DIBI's iron sequestration activity in the nares is supported by the reported upregulated bacterial expression of IsdA, a cell wall component indicative of iron-limited conditions (18), as well as the overall upregulation of iron acquisition systems during nares carriage (19,20). Our results suggest that iron supply to S. aureus isolates within the nares is a key determinant for establishment and maintenance of carriage and that DIBI appears to aid natural host iron-withdrawal mechanisms to suppress carriage.…”
mentioning
confidence: 93%
“…4 ). Consistent with these various studies, S. aureus has been shown to upregulate its iron acquisition mechanisms during growth in the nares (Chaves-Moreno et al 2016 ) and during systemic infection (Bacconi et al 2017 ).
Fig.
…”
Section: Antibiotic Resistance and Microbial Iron Needsmentioning
confidence: 59%